Prevalence and allergy-related risk factors of overactive bladder in children in Northeast China - Zheng, Yue; Yin, Lu; Wang, Xiuli; Zhao, Chengguang; Du, Yue (Frontiers in Public Health, 2024)
The objective of this study was to investigate the prevalence of overactive bladder (OAB) and risk factors related to allergy for OAB among children in Northeastern China.Methods: A community survey on OAB was conducted in Northeast China from April 1, 2022, to April 30, 2022. The survey targeted children aged 5 to 14 and utilized questionnaires. A total of 1,394 children were enrolled, and their parents were requested to fill out a questionnaire to provide the children's basic information. This encompassed details regarding the presence or absence of urgent urination unrelated to urinary tract infection, urinary tract infection, allergic rhinitis, asthma or cough variant asthma, atopic dermatitis, anaphylactic conjunctivitis, urticaria, constipation, and attention deficit hyperactivity disorder (ADHD). The prevalence of OAB was calculated. The chi-squared test was used to analyze OAB-related factors, which were subsequently included in the logistic regression model for multi-factor analysis.The overall OAB prevalence was 10.7% (120/1121), including 47 mild cases (39.2%), 71 moderate cases (59.1%) and 2 severe cases (1.7%). The OAB prevalence decreased with age (P < 0.05). The risk factors associated with OAB were allergic asthma (OR=1.87, 95%Cl:1.12-3.13), atopic dermatitis (OR=2.45, 95%Cl:1.61-3.73), anaphylactic conjunctivitis (OR=1.61, 95%Cl:1.07-2.42), and urticaria (OR=1.93 , 95%Cl:1.40-2.66).Conclusions: OAB prevalence among children in Northeastern China is 10.7%, and its risk factors are allergic asthma, anaphylactic conjunctivitis, urticaria, and atopic dermatitis. The identification of allergy-related risk factors may provide new ideas for the prevention and treatment of OAB.